Pengaruh biaya operasional, Dana Pihak Ketiga (DPK), dan Non Peforming Financing (NPF) terhadap margin murabahah pada bank umum syariah di Indonesia - Zulpahmi, Zulpahmi; Rizqiana, Eka (Jurnal Ekonomi & Keuangan Islam, 2018)
This study aims to analyze and determine whether there is a direct effect of operating expense, third fund party and non-peforming financing to margin murabahah in Sharia commercial bank in Indonesia. Research population is Sharia commercial banks in Indonesia, while sampling technique used is purposive sampling with selected sample of 5 Sharia commercial banks. Data collection technique in this study is a document review of company’s Annual Report. However, techniques of processing and analyzing data are accounting analysis, descriptive statistical analysis, multiple linear regression analysis, classical assumption test, coefficient determinant coefficient analysis and hypothesis test using SPSS version 20. Based on the partial test, operating expense and third party fund have a positive and significant effect on margin murabahah while non-peforming financing has a negative and insignificant effect on margin murabahah. However, simultaneously operating expense, third party fund and non peforming financing have a positive and significant impact on margin murabahah.